Impact of Profitability and Leverage on Tax Avoidance; Corporate Social Responsibility (CSR) as Mediating Variable - Triana Friskila; Jaeni Jaeni (Jurnal Akuntansi dan Perpajakan, 2022)
The purpose of this research is to analyze the factors that influence tax avoidance. The population of this study are coal mining companies listed on the IDX in 2017-2021. The research sample consisted of the financial reports and annual reports of companies listed on the IDX from 2017 to 2021. The purposive sampling technique was applied in this study, generating 100 observational data from the acquisition of 20 organizations over the 5-year study period. SPSS program version 25.0 is used in this research analysis. Based on the results of the study, profitability has no significant negative effect on corporate social responsibility, while leverage has no significant positive effect on corporate social responsibility. In addition, profitability has no significant negative effect on Tax Avoidance, tax avoidance has a significant positive effect on leverage, and corporate social responsibility has no significant positive effect on Tax Avoidance. The mediation results in this study indicate that Corporate Social Responsibility is unable to mediate between profitability and leverage on Tax Avoidance.Keywords: Leverage; Tax Avoidance; Profitability; Corporate social responsibility.